Answer:
do ur test by ur own understanding... xD
Step-by-step explanation:
<h3>all the natural numbers can be expressed in the form of the product of its prime factors.</h3>
The first thing we have to do is to calculate the
midpoint of the min and max speeds. We are given that the min and max is 74 and
95 respectively. The midpoint is then calculated as (max+min) / 2. Therefore:
midpoint = (74 + 95) / 2 = 84.5
Next, we calculate the distance from the midpoint to the
endpoint by doing subtraction. Therefore:
min endpoint: 84.5 – 74 = 10.5
max endpoint: 95 – 84.5 = 10.5
Now we know that v minus the midpoint will equal the
distance such that:
| v - midpoint | = distance.
To our problem,
| v – 84.5 | = 10.5
Answer:
1.
= ![\frac{2x^2+10x+6}{(x+3)(x+5)}\\](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2%2B10x%2B6%7D%7B%28x%2B3%29%28x%2B5%29%7D%5C%5C)
2.
= ![\frac{1}{(x+2)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x%2B2%29%28x-4%29%7D)
3.
= ![\frac{-3x^2-7x-4}{(x+3)(x-3)(x-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B-3x%5E2-7x-4%7D%7B%28x%2B3%29%28x-3%29%28x-2%29%7D)
4.
= ![\frac{1}{(x-2)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-2%29%28x-4%29%7D)
Step-by-step explanation:
1. ![\frac{x}{x+3}+\frac{x+2}{x+5}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7Bx%2B3%7D%2B%5Cfrac%7Bx%2B2%7D%7Bx%2B5%7D)
Taking LCM of (x+3) and (x+5) which is: (x+3)(x+5)
![=\frac{x(x+5)+(x+2)(x+3)}{(x+3)(x+5)}\\=\frac{x^2+5x+(x)(x+3)+2(x+3)}{(x+3)(x+5)} \\=\frac{x^2+5x+x^2+3x+2x+6}{(x+3)(x+5)} \\=\frac{x^2+x^2+5x+3x+2x+6}{(x+3)(x+5)} \\=\frac{2x^2+10x+6}{(x+3)(x+5)}\\](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bx%28x%2B5%29%2B%28x%2B2%29%28x%2B3%29%7D%7B%28x%2B3%29%28x%2B5%29%7D%5C%5C%3D%5Cfrac%7Bx%5E2%2B5x%2B%28x%29%28x%2B3%29%2B2%28x%2B3%29%7D%7B%28x%2B3%29%28x%2B5%29%7D%20%5C%5C%3D%5Cfrac%7Bx%5E2%2B5x%2Bx%5E2%2B3x%2B2x%2B6%7D%7B%28x%2B3%29%28x%2B5%29%7D%20%5C%5C%3D%5Cfrac%7Bx%5E2%2Bx%5E2%2B5x%2B3x%2B2x%2B6%7D%7B%28x%2B3%29%28x%2B5%29%7D%20%5C%5C%3D%5Cfrac%7B2x%5E2%2B10x%2B6%7D%7B%28x%2B3%29%28x%2B5%29%7D%5C%5C)
Prove closure: The value of x≠-3 and x≠-5 because if there values are -3 and -5 then the denominator will be zero.
2. ![\frac{x+4}{x^2+5x+6}*\frac{x+3}{x^2-16}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B4%7D%7Bx%5E2%2B5x%2B6%7D%2A%5Cfrac%7Bx%2B3%7D%7Bx%5E2-16%7D)
Factors of x^2-16 = (x)^2 -(4)^2 = (x-4)(x+4)
Factors of x^2+5x+6 = x^2+3x+2x+6 = x(x+3)+2(x+3) =(x+2)(x+3)
Putting factors
![=\frac{x+4}{(x+3)(x+2)}*\frac{x+3}{(x-4)(x+4)}\\\\=\frac{1}{(x+2)(x-4)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bx%2B4%7D%7B%28x%2B3%29%28x%2B2%29%7D%2A%5Cfrac%7Bx%2B3%7D%7B%28x-4%29%28x%2B4%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B1%7D%7B%28x%2B2%29%28x-4%29%7D)
Prove closure: The value of x≠-2 and x≠4 because if there values are -2 and 4 then the denominator will be zero.
3. ![\frac{2}{x^2-9}-\frac{3x}{x^2-5x+6}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bx%5E2-9%7D-%5Cfrac%7B3x%7D%7Bx%5E2-5x%2B6%7D)
Factors of x^2-9 = (x)^2-(3)^2 = (x-3)(x+3)
Factors of x^2-5x+6 = x^2-2x-3x+6 = x(x-2)+3(x-2) =(x-2)(x+3)
Putting factors
![\frac{2}{(x+3)(x-3)}-\frac{3x}{(x+3)(x-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B%28x%2B3%29%28x-3%29%7D-%5Cfrac%7B3x%7D%7B%28x%2B3%29%28x-2%29%7D)
Taking LCM of (x-3)(x+3) and (x-2)(x+3) we get (x-3)(x+3)(x-2)
![\frac{2(x-2)-3x(x+3)(x-3)}{(x+3)(x-3)(x-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%28x-2%29-3x%28x%2B3%29%28x-3%29%7D%7B%28x%2B3%29%28x-3%29%28x-2%29%7D)
![=\frac{2(x-2)-3x(x+3)}{(x+3)(x-3)(x-2)}\\=\frac{2x-4-3x^2-9x}{(x+3)(x-3)(x-2)}\\=\frac{-3x^2-9x+2x-4}{(x+3)(x-3)(x-2)}\\=\frac{-3x^2-7x-4}{(x+3)(x-3)(x-2)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2%28x-2%29-3x%28x%2B3%29%7D%7B%28x%2B3%29%28x-3%29%28x-2%29%7D%5C%5C%3D%5Cfrac%7B2x-4-3x%5E2-9x%7D%7B%28x%2B3%29%28x-3%29%28x-2%29%7D%5C%5C%3D%5Cfrac%7B-3x%5E2-9x%2B2x-4%7D%7B%28x%2B3%29%28x-3%29%28x-2%29%7D%5C%5C%3D%5Cfrac%7B-3x%5E2-7x-4%7D%7B%28x%2B3%29%28x-3%29%28x-2%29%7D)
Prove closure: The value of x≠3 and x≠-3 and x≠2 because if there values are -3,3 and 2 then the denominator will be zero.
4. ![\frac{x+4}{x^2-5x+6}\div\frac{x^2-16}{x+3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B4%7D%7Bx%5E2-5x%2B6%7D%5Cdiv%5Cfrac%7Bx%5E2-16%7D%7Bx%2B3%7D)
Factors of x^2-5x+6 = x^2-3x-2x+6 = x(x-3)-2(x-3) = (x-2)(x-3)
Factors of x^2-16 = (x)^2 -(4)^2 = (x-4)(x+4)
![\frac{x+4}{(x-2)(x+3)}\div\frac{(x-4)(x+4)}{x+3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B4%7D%7B%28x-2%29%28x%2B3%29%7D%5Cdiv%5Cfrac%7B%28x-4%29%28x%2B4%29%7D%7Bx%2B3%7D)
Converting ÷ sign into multiplication we will take reciprocal of the second term
![=\frac{x+4}{(x-2)(x+3)}*\frac{x+3}{(x-4)(x+4)}\\=\frac{1}{(x-2)(x-4)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bx%2B4%7D%7B%28x-2%29%28x%2B3%29%7D%2A%5Cfrac%7Bx%2B3%7D%7B%28x-4%29%28x%2B4%29%7D%5C%5C%3D%5Cfrac%7B1%7D%7B%28x-2%29%28x-4%29%7D)
Prove Closure: The value of x≠2 and x≠4 because if there values are 2 and 4 then the denominator will be zero.